Development of Lightweight Steel Framed Construction Systems for Nearly-Zero Energy Buildings - Jelčić Rukavina, Marija; Skejić, Davor; Kralj, Anton; Ščapec, Tomislav; Milovanović, Bojan (Buildings (Basel), 2022)
Light steel frame (LSF) building systems offer high structural resilience, lower costs due to fast prefabrication, and high ability to recycle and reuse. The main goal of this paper was to provide state-of-the-art main components for such systems with the intention to be implemented for use in nearly-zero energy buildings (NZEBs). A brief historical outline of the development of LSF systems was given, and the key parameters affecting the design and use of LSF systems were discussed. The influence of the individual components of the LSF system (steel studs, sheathing boards, and insulation materials) was then thoroughly discussed in light of relevant research on energy efficiency and other important properties (such as sound protection and fire resistance). Web of Science and Scopus databases were used for this purpose, using relevant key words: LSF, energy efficiency, sheathing boards, steel studs, insulation, etc. Several research gaps were identified that could be used for development and future research on new LSF systems. Finally, based on the analysis of each component, an innovative LSF composite wall panel was proposed which will be the subject of the authors’ future research. Conducted preliminary analysis showed low thermal transmittance of the system and indicates the path of its further research.